Kepemimpinan Kiai Dalam Pengembangan Kurikulum TMI Studi Kasus di Pondok Pesantren Wali Songo Ngabar - Ikhsan Wahkid Saputra; Ali Rohmad; Dien Majid Ikhwan; Elhaq Z.R (Journal Islamic Education, 2025)
The leadership of the kiai in curriculum development at the "Wali Songo" Ngabar Islamic Boarding School plays a crucial role in creating an integrated and relevant education system for the Industrial Revolution 5.0 era. This study employed a descriptive qualitative approach with data triangulation through interviews, observation, and documentation. The results show that the kiai act as leaders, educators, and role models in developing a curriculum that integrates Islamic values and the formal curriculum. Strategies implemented include regular evaluation, the use of digital technology, and collaboration with national and international educational institutions. Curriculum implementation is also supported by adequate infrastructure, creating synergy between academic needs and character development. This study emphasizes the importance of responsive leadership in addressing the challenges of education in Islamic boarding schools in the modern era.